Inflation persistence in the European Union, the euro area, and the United States - Gregory Gadzinski; Fabrice Orlandi (European Central Bank (ECB), 2004)
In this paper we report results on inflation persistence using 79 inflation series covering the EU countries, the euro area and the US for five different inflation variables. The picture that emerges is one of moderate inflation persistence across the board. In particular we find euro area inflation persistence to be broadly in line with US inflation persistence. The issue of allowing for intercept dummies in the underlying inflation models is found to be of paramount importance to avoid overestimation of the level of persistence. The use of alternative measures of persistence is found to be commendable on the grounds that they complement each other in practice.
Keywords: E31; E52; C22; C12; 330; Inflation Dynamics; median unbiased estimates; Structural change